Strategi Pemasaran Dalam Upaya Meningkatkan Jumlah Anggota Produk Simpan Pinjam Pada Koperasi Jasa Bintang Muda 88 Di Kecamatan Makale Kabupaten Tana Toraja - Yovita Yovita; Abedneigo. C. Rambulangi; Mey. E. Limbongan (Universitas Kristen Indonesia Toraja, 2023)
The purpose of this study was to find out what marketing strategies were carried out by the Bintang Muda 88 service cooperative in increasing the number of savings and loan members and to explain the application of the savings and loan product marketing strategy that was determined to have and impact on increasing the number of members in the Bintang Muda 88 service cooperative. The type of research used was qualitative with the number of research informants 5 people. The research results obtained by setting the 4P strategy (Product, Price, Place and Promotion) are proven to be able to increase the number of savings and loan product members in the Bintang muda 88 service cooperative.